FcγR-Binding Is an Important Functional Attribute for Immune Checkpoint Antibodies in Cancer Immunotherapy - Chen, Xin; Song, Xiaomin; Li, Kang; Zhang, Tong (Frontiers in Immunology, 2019)
T cells play critical roles in anti-tumor immunity. Up-regulation of immune checkpoint molecules (PD-1, PD-L1, CTLA-4, TIM-3, Lag-3, TIGIT, CD73, VISTA, B7-H3) in the tumor microenvironment is an important mechanism that restrains effector T cells from the anti-tumor activity. To date, immune checkpoint antibodies have demonstrated significant clinical benefits for cancer patients treated with mono- or combination immunotherapies. However, many tumors do not respond to the treatment well, and merely blocking the immune suppression pathways by checkpoint-regulatory antibodies may not render optimal tumor growth inhibition. Binding of the antibody Fc-hinge region to Fc gamma receptors (FcγRs) has been shown to exert a profound impact on antibody function and in vivo efficacy. Investigation of immune checkpoint antibodies regarding their effector functions and impact on therapeutic efficacy has gained more attention in recent years. In this review, we discuss Fc variants of antibodies against immune checkpoint targets and the potential mechanisms of how FcγR-binding could influence the anti-tumor activity of these antibodies.